Effects of bronchoalveolar lavage on Mycoplasma Pneumoniae pneumonia: A propensity score matched-cohort study - Lu, Jinmiao; Zhang, Junqi; Wang, Guangfei; Zhang, Xiaobo; Li, Zhiping (Frontiers in Pediatrics, 2023)
Background The purpose of this study was to evaluate the efficacy and safety of BAL in treating MPP. Methods From January 2013 to January 2019, 1,689 pediatric patients with MPP were analyzed retrospectively. Patients were subdivided into BAL group and non-BAL group according to whether they received BAL treatment within seven days after admission. The propensity score matching method matched patients' baseline characteristics (1:1). The primary outcomes were hospital stays and the cure rate. Secondary outcomes included mortality, co-infection, repeat hospitalization within 30 days, and total cost of treatment. Results After matching, 524 patients (BAL: 262; control: 262) were recorded. The BAL group had significantly shorter hospital stays (OR: 0.5, 95% CI: 0.4–0.7). Meanwhile, BAL did not significantly modify the cost, co-infection rate, and mortality. In subgroup analyses, the group with BAL intervention within three days had a significantly shorter hospital stay (OR: 0.4, 95% CI: 0.3–0.5) compared with the group with BAL intervention three days after admission. Conclusions Early BAL intervention is a better treatment than conventional drug therapy alone, and no significant complications were seen in this study. BAL intervention has an excellent clinical benefit. The earlier the intervention, the better the effect.